ОЦЕНКА СТАБИЛИЗИРУЮЩИХ КОМПОЗИЦИЙ ДЛЯ ЛИОФИЛИЗАЦИИ И ХРАНЕНИЯ ВАКЦИНЫ ПРОТИВ ЧУМЫ МЕЛКИХ ЖВАЧНЫХ С ДЛИТЕЛЬНЫМ СРОКОМ ГОДНОСТИ - Ж. Саметова; Ж. Аманова; А. Үсембай; Р. Абитаев; Ш. Тұрыскелді; Ж. Кондибаева; Е. Булатов (Animal Health and Biosafety, 2026)
Peste des Petits Ruminants is a significant transboundary viral disease of small ruminants requiring stable live vaccines for effective control. The aim of this study was to select an optimal stabilizing formulation for long-term preservation of a live attenuated vaccine based on the Nigeria 75/1 strain. Six protein–carbohydrate formulations differing in composition and concentration were evaluated. Vaccine samples were subjected to lyophilization, followed by assessment of infectious activity before and after freeze-drying. Stability was monitored during storage at +2–4 °C for 36 months, including infectious titer, residual moisture, reconstitution time, and physicochemical properties. Lyophilization caused a slight reduction in infectious titer within acceptable limits. Formulations No. 2, 5, and 6 demonstrated superior protective effects. The formulation containing 5% peptone and 3% sucrose was identified as optimal, ensuring minimal loss of viral activity (